DIAGNOSTIC ACCURACY OF 99mTc METHOXYISOBUTYLISONITRILE (MIBI) SCINTIMAMMOGRAPHY IN DETECTION OF BREAST CANCER - Sharoon, Rebecca; Hussain, Fida; Ibrahim, Taseer; Raza, Mehdi; Seher, Saima (Pakistan Armed Forces Medical Journal, 2021)
Objective: To evaluate the diagnostic accuracy of Scintimammography as a reliable diagnostic modality for detecting carcinoma breast keeping histopathology as a gold standard for final diagnosis. Study Design: Cross sectional validation study. Place and Duration of Study: Nuclear Medical Centre (NMC), Armed Forces Institute of Pathology (AFIP) Rawalpindi, from Oct 2016 to Apr 2017. Methodology: 738-1100 MBq (20-30 mCi) of 99mTc methoxyisobutylisonitrile (MIBI) was injected intravenously in the contralateral arm to the affected breast, in case of bilateral breast lumps tracer was injected in foot. Planar Images were acquired in prone and supine positions at 20 and 60 min. Gamma camera was equipped with low energy all-purpose collimator. Photopeak centered at 140 Kev (Kiloelectron volt) with 20% window, and matrix size of 256X256 pixels. Results: Total 96 patients were included in the study. After scintimammography each patient underwent FNAC/ TRUCUT for histopathological diagnosis. The age of patients ranged from 20-74 years. The mean age of presentation was 43.22 ± 12.59 years. Diagnostic accuracy was calculated for 96 patients. Fifty three had true positive (TP) while 37 had true negative (TN) results. The sensitivity, specificity, positive predictive values (PPV) and negative predictive values (NPV) of the study was 98.1, 88.1, 91.4, 97.4% respectively and an accuracy of 93.75%. Conclusion: This study has shown an excellent sensitivity, specificity in detection of malignant mitotic lesions of breast, although any test with <100% negative predictive values is not reliable but a negative predictive value >85% is worth trying for especially in patients where Mammography may not be of much benefit. The patient will benefit from non-invasive, nonpainful modality with less need for biopsy.